Salt glands of Armeria canescens (Host) Boiss.: Morphological and functional aspects. (1st November 2016) - Scassellati, E.; Pasqua, G.; Valletta, A.; Abbate, G.
Abstract: The morphology and functionality of salt glands in four Italian Armeria canescens populations were investigated. Microscopic analysis showed that salt glands consist of 16 cells arranged in four quadrants, including four subsidiary cells and 12 gland cells. The main secreted elements are K, Ca and Cl, although qualitative and quantitative differences were observed between gland and subsidiary cells. Soil characteristics like texture, pH and C/N ratio were shown to vary between population sites. The highest number of glands per leaf area was found in plants from Ca-rich sites. Although A. canescens is not a halophilous species, its salt glands were revealed to be active, suggesting that they could represent an ancestral character.